A biased firm in a market with complementary products. A note on the welfare effects - Clemens Buchen; Alberto Palermo (Scottish Journal of Political Economy, 2019)
We analyse a duopoly setting with complementary products, in which a firm has a bias about its absolute advantage. We show that the bias can internalize parts of the negative externality that the complementarity of goods creates implying a higher producer's surplus. Moreover, we analyse additional conditions, which lead to an increase in the consumer's surplus. Counterintuitively, we show that the presence of a bias can lead to a positive welfare effect.
Keywords: 330; Bias; complementary products; oligopoly